Adaptation and forage productivity of cool‐season grasses in the central USA. Issue 2 (12th June 2021) - Vogel, Kenneth P.; Mitchell, Rob
Abstract: Cool‐season grass species (18) and cultivars (85) were evaluated for use in seeded grasslands in the tallgrass prairie and shortgrass steppe ecoregions of the central United States at the test locations of Ithaca and Sidney, NE, respectively. Both native and introduced grasses were evaluated in sward trails. Significant differences existed among species and cultivars for all traits evaluated except for in vitro dry matter digestibility (IVDMD) among cultivars within species at Sidney. The grasses that had the best establishment, persistence, and forage yields in the Ithaca trial were introduced wheatgrass ( Thinopyrum ) and bromegrass ( Bromus ) species. At the Sidney location, the best species using the same criteria were wheatgrasses ( Thinopyrum, Agropryon, Pascopyrum, and Elymus spp.) and wildryes ( Psathyrostachys ). The only native grasses that were marginally competitive with the introduced grasses were western wheatgrass [ Pascopyrum smithii (Rydb.) A. Löve] and thickspike wheatgrass [ Elymus macrourus (Turcz.) Tzvelev] at the Sidney location and western wheatgrass at Ithaca. The study was the largest cool‐season forage grass multispecies and cultivar sward evaluation to date in these two major land areas. The superior species and cultivars that were identified represent the best cool‐season grasses available for restoring marginal croplands to grazed grasslands in these two major land areas. Core Ideas: Grasses used in seeded grasslands in the central United States need several essential traits. Essential traits are establishment, persistence, forage yield, and quality. Grasses from similar ecoregions of Eurasia were superior to native species for these traits. The best species and cultivars differed between the two tested ecoregions.